Integration of Islamic Spiritual Care (ISC), Service Quality and Patient Loyalty A Cross-Sectional Study at One of The Islamic Hospitals In Indonesia - Muhammad Sadik Sahil; Iwan Muhamad Ramdan; Nur Rohmah (Public Health Undergraduate Program, Faculty of Health Science, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Background: Islamic spiritual care (ISC) is a holistic religious health service based on Islamic values ​​that emphasizes empathy and friendliness and provides space for patients to perform worship during treatment. This study aims to analyze the correlation between integrating of ISC with the quality of service and patient loyalty, and to determine the most dominant variables influencing patient loyalty. Method: A quantitative study with a cross-sectional design was conducted on 176 outpatients, during February–April 2025 on Siaga Al Munawwarah Islamic Hospital, Samarinda, Indonesia. The measuring instruments used consisted of the Islamic Spiritual Care questionnaire (ISCQ), SERVQUAL (Service Quality Questionnaire), and HCAHPS (Hospital Consumer Assessment of Healthcare Providers and Systems), which have been proven valid and reliable. Data analysis used the Spearman Rank test and Binary logistic regression Results: The integration of ISCand service quality as good (54,5%) and showed good loyalty (51.7%). There was a significant relationship between integration of ISC and service quality (p = 0.000; r = 0.905), there was a significant relationship between integration of ISC and patient loyalty (p = 0.000; r = 0.787), and there was a significant relationship between service quality and patient loyalty (p = 0.000; r = 0.817). Patient service quality is the most dominant variable influencing patient loyalty (POR = 10.271). Conclusion: Integration of ISC affects service quality and patient loyalty. This finding indicates that ISC needs to be implemented comprehensively and continuously at Siaga Al Munawarrah Islamic Hospital.